Adsorption Behaviour of Chromium(VI) onto Surface Modified Sugarcane Waste - Ghimire, Kedar Nath; Wagle, Deepak; Shrestha, Suman Lal (Tribhuvan University Journal, 2013)
An effective chemically modified adsorbent based on sugarcane waste has been prepared by treating with concentrated sulphuric acid in 2:1weight/volume ratio. Thus prepared adsorbent has been found to be effective in the adsorption of chromium from aqueous medium. The efficacy of the adsorbent in the removal of chromium was evaluated by batch adsorption method. The effect of initial concentration, contact time and pH of the solution was investigated. The maximum adsorption capacity onto this adsorbent was found to be 195 mg/g at their optimal pH 1 at which unmodified bagasse has only 58 mg/g. The characterization of adsorbent was done by determining surface area and Boehm’s titration method. Freundlich isotherm and pseudo-second order kinetic model gave better explanation of the adsorption process.